Brazilian franchisor: Entry and operation of internationalized franchise - Aguiar, Helder de Souza; Luppe, Marcos Roberto; Nascimento, Paulo Tromboni de Souza (Internext, 2017)
This study aimed to compare the entry and operations strategies of franchisors of developed countries into foreign countries with Brazilian counterparts. Were there significant differences? An exploratory study was conducted with 16 international franchisors operating in Brazil and 31 Brazilian franchisors operating abroad. The results show that international franchisors operating abroad prefer to use a subsidiary in the destination country. At the same time, this strategy is little used by Brazilian franchisors, which prefer the strategy of direct franchises. For data collection, 47 directors or managers of the international expansion of Brazilian companies and the expansion directors of the international companies which operates in Brazil were interviewed. Although more expensive, the subsidiary in the target country offers greater control over the expansion of business reducing the problems caused by the distance of the country of origin. For the management of franchisors, this paper points out that the subsidiary is a natural evolution of entry and operation mode when it is desired or it is needed to control the expansion of networks in other countries. Thus, managers of franchisors in emerging countries should carefully examine the subsidiary option in the target country when their company considers accelerating international growth.